Effect of standardized fluid management on cardiac function after CRS + HIPEC in patients with PMP: a single-center case-control study. (31st December 2023) - Yang, Rui; Su, Yan-Dong; Liu, Gang; Yu, Yang; Li, Xin-Bao; Zhao, Xin; Ji, Zhong-He; Ma, Ru; Yang, Zhi-Ran; Lin, Yu-Lin; Wu, He-Liang; Li, Yan
Abstract: Objective: To investigate the effects of standardized fluid management (SFM) on cardiac function in patients with pseudomyxoma peritonei (PMP) after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Method: Patients with PMP who underwent CRS + HIPEC at our center were retrospectively analyzed. The patients were divided into control and study groups according to whether SFM was applied after CRS + HIPEC. We compared the preoperative and postoperative cardiac and renal function parameters, daily fluid volume three days after CRS, and cardiovascular-related adverse events. Univariate and multivariate analyses were performed to identify the indicators affecting clinical prognosis. Result: Among the 104 patients, 42 (40.4%) were in the control group and 62 (59.6%) in the study group. There were no statistically significant differences between the two groups in the main clinicopathological characteristics, preoperative cardiac and renal function parameters, and CRS + HIPEC-related indicators. The incidences of cardiac troponin I (CTNI) > upper limit of normal (ULN), >2 × ULN, >3 × ULN, serum creatinine > ULN, and blood urea nitrogen > ULN were higher in the control group than in the study group ( p  < 0.05). The median daily fluid volume of the control group was higher than that of the study group 3 days after CRS ( p  < 0.05). Postoperative CTNI > 2 × ULN was an independent risk factor for serious circulatory adverse events. Survival analysis revealed pathological grading, completeness of cytoreduction score, and postoperative CTNI > ULN as independent prognostic factors. Conclusions: SFM after CRS + HIPEC in patients with PMP may reduce cardiovascular adverse events risk and improve clinical outcomes.